Preparation method and application of bacterial cellulose based composite nano generator
By using bacterial cellulose-based composite nanogenerators in power transformers, the problem of difficulty in monitoring and real-time tracking of leakage magnetic fields in the existing technology is solved, achieving accurate real-time monitoring of leakage magnetic fields in power transformers, and enhancing the safety of the power system. sex and stability.
Patent Information
- Application Number
- CN202411485192.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-23
Smart Images

Figure CN119306976A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanogenerators and power monitoring, and in particular to a preparation method and application of a bacterial cellulose-based composite nanogenerator. Background Art
[0002] As the core equipment for power transmission and distribution, the safe and stable operation of power transformers is a key factor in ensuring the overall reliability and efficiency of the power grid. Transformer leakage magnetic field is the magnetic field leakage phenomenon generated during the operation of the transformer. It may not only interfere with the surrounding electromagnetic environment, but also have adverse effects on nearby electrical equipment, communication lines, etc., and even accelerate equipment aging and increase the risk of failure.
[0003] Different types of transformer faults (such as winding short circuit, core fault, insulation degradation, etc.) will cause significant changes in the leakage magnetic field characteristics. These changes, such as the increase or decrease of magnetic field strength and the variation of distribution form, make it possible to identify potential transformer faults by monitoring the leakage magnetic field. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a bacterial cellulose-based composite nanogenerator, which utilizes the excellent mechanical properties of bacterial cellulose composite materials and the special effects of nanomaterials to convert mechanical energy and electromagnetic energy into electrical energy, and realizes real-time monitoring of the transformer leakage magnetic field by monitoring electrical energy fluctuations.
[0005] To achieve the above object, the present invention provides a method for preparing a bacterial cellulose-based composite nanogenerator, comprising the following steps: S1. Graphene oxide and cobalt ferrite are embedded in bacterial cellulose matrix through solution blending technology to prepare a structurally stable composite material; S2. Systematically evaluate the electromagnetic properties, triboelectric properties and mechanical stability of composite materials of various formulas to select the optimal formula; S3. Prepare composite nanogenerators using composite materials with optimal formulas screened out.
[0006] Preferably, the S1 specifically includes: S11, cutting the bacterial cellulose hydrogel into block samples of 2×2 cm, stirring for 30 min using a high shear dispersing homogenizer to prepare a 10 mg / mL bacterial cellulose aqueous solution; S12, dispersing predetermined amounts of graphene oxide powder and cobalt ferrite powder in appropriate solvents to form uniform graphene oxide suspension and cobalt ferrite suspension; S13, mixing the prepared graphene oxide suspension and the cobalt ferrite suspension in an optimal ratio, and further dispersing them by ultrasonic treatment to obtain a mixed suspension in which nanoparticles are evenly distributed; S14, slowly adding the obtained mixed suspension into the bacterial cellulose aqueous solution, and continuing stirring to make the graphene oxide and cobalt ferrite evenly embedded in the bacterial cellulose matrix to obtain a mixed solution; S15, pouring the mixed solution into a mold for vacuum defoaming treatment for 10 minutes, and performing heating and drying treatment, thereby preparing a composite material with stable structure and excellent performance.
[0007] Preferably, the limiting conditions for uniformly embedding graphene oxide and cobalt ferrite in the bacterial cellulose matrix in S14 include: the content of graphene oxide is limited to a range of 0.2% to 1.2% of the total mass of the composite material; the content of cobalt ferrite is limited to a range of 0.2% to 1% of the total mass of the composite material.
[0008] Preferably, the limiting conditions for uniformly embedding graphene oxide and cobalt ferrite in the bacterial cellulose matrix in S14 include: the content of graphene oxide is limited to the range of 0.5% to 0.8% of the total mass of the composite material; the content of cobalt ferrite is limited to the range of 0.2% to 0.6% of the total mass of the composite material.
[0009] Preferably, S2 specifically includes: S21. Conducting systematic performance tests on the composite materials prepared by each formula, including electromagnetic performance test, dielectric performance test, triboelectric performance test and mechanical performance test; S22. Statistically analyze the results of the performance test, and use a suitable mathematical model or optimization algorithm to find the best balance between electromagnetic performance, triboelectric performance and mechanical stability, so as to screen out the optimal formula; S23. Conduct stability and durability tests on the composite materials with the best formula to ensure the reliability and stability of the test results.
[0010] Preferably, the S21 includes the following operations before the triboelectric performance test: A high-performance vertical contact-separation mode friction nanogenerator structure is constructed, and the composite material is used as the positive friction layer material. By comparing the output performance or surface energy of the friction nanogenerator, the appropriate negative friction layer material is selected.
[0011] Preferably, the positive friction layer material and the negative friction layer material are circular samples with a diameter of 55 mm, and the negative friction layer material is one of ethylene fluoride copolymer, polyimide, and polytetrafluoroethylene.
[0012] Preferably, S3 specifically includes: S31, processing the composite material with the best formula screened out into a friction layer with a specific shape and size; S32. Design and prepare electromagnetic induction coils, and select appropriate wire diameters, number of turns, and layout; S33, assembling the friction layer and the electromagnetic induction coil according to a preset layout and position to form a composite structure; S34, electrically connecting and packaging the composite structure to obtain a composite nanogenerator.
[0013] The present invention provides an application of a composite nanogenerator based on a bacterial fiber composite material, and an application of the composite nanogenerator prepared by the above-mentioned preparation method in transformer leakage magnetic field monitoring.
[0014] The present invention provides a device for monitoring leakage magnetic field of a power transformer, comprising the following devices: A composite nanogenerator prepared by the above-mentioned preparation method; Signal processing system, used to collect and analyze the power fluctuation data output by the generator; A processor, for processing the signal and converting the data into status information of the transformer leakage magnetic field; The operation interface is used to display the real-time data and historical trends of the transformer leakage magnetic field, as well as to perform fault warning and performance evaluation.
[0015] Therefore, the present invention adopts the above-mentioned bacterial cellulose-based composite nanogenerator preparation method and application, which has the following beneficial effects: (1) The innovative integration of electromagnetic and triboelectric effects realizes a dual energy conversion mechanism, significantly improving energy collection efficiency and system stability. The generator uses the high mechanical strength and biocompatibility of bacterial cellulose to prepare a composite material with stable structure and excellent performance, realizing accurate real-time monitoring of the leakage magnetic field of the power transformer.
[0016] (2) It not only enhances the safety and stability of the power system, but also expands the application scope of electromagnetic field monitoring. At the same time, the characteristics of its bio-based materials are in line with the trend of green development, promoting resource recycling and sustainable development, and has great value in the field of power monitoring and new energy materials.
[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a flow chart of a preparation method and application example of a bacterial cellulose-based composite nanogenerator of the present invention; Figure 2It is a preparation method of a bacterial cellulose-based composite nanogenerator of the present invention and the hysteresis loop of the composite material under different formulations of the application embodiment; Figure 3 It is a schematic diagram of the structure of a friction-electromagnetic composite nanogenerator provided by a preparation method and application example of a bacterial cellulose-based composite nanogenerator of the present invention; Figure 4 The present invention discloses a method for preparing a bacterial cellulose-based composite nanogenerator and a flow chart of a power transformer leakage magnetic field monitoring state provided in an application example. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0020] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0021] Example like Figure 1 As shown, the present invention provides a method for preparing a bacterial cellulose-based composite nanogenerator, comprising the following steps: S1. Graphene oxide and cobalt ferrite are embedded in bacterial cellulose matrix through solution blending technology to prepare a structurally stable composite material; Among them, bacterial cellulose has excellent mechanical properties, high porosity and good biocompatibility, so it is used as the substrate; the addition of graphene oxide significantly improves the conductivity and mechanical strength of the composite material; cobalt ferrite as a magnetic material gives the composite material the property of being sensitive to electromagnetic fields.
[0022] The specific operations of S1 are: S11, cutting the bacterial cellulose hydrogel into block samples of 2×2 cm, stirring for 30 min using a high shear dispersing homogenizer to prepare a 10 mg / mL bacterial cellulose aqueous solution; S12, successively dispersing predetermined amounts of graphene oxide powder and cobalt ferrite powder in appropriate solvents, respectively, and using a high-efficiency stirring device or ultrasonic assistance to form a uniform and stable graphene oxide suspension and cobalt ferrite suspension; S13, mixing the prepared graphene oxide suspension and cobalt ferrite suspension in an optimal ratio, and further dispersing them by ultrasonic treatment to obtain a mixed suspension in which nanoparticles are evenly distributed; wherein the ultrasonic treatment is performed intermittently to avoid overheating and particle aggregation; S14, slowly adding the obtained mixed suspension into the bacterial cellulose aqueous solution, and continuing stirring to make the graphene oxide and cobalt ferrite evenly embedded in the bacterial cellulose matrix to obtain a mixed solution; S15. Pour the mixed solution into a mold for vacuum defoaming treatment for 10 minutes, and dry it at 60° C. for 12 hours, thereby preparing a composite material with stable structure and excellent performance.
[0023] S2. The system evaluates the electromagnetic properties, triboelectric properties and mechanical stability of each composite material to select the optimal formula. The specific operations are as follows: S21. Conducting systematic performance tests on the composite materials prepared by each formula, including electromagnetic performance test, dielectric performance test, triboelectric performance test, and mechanical performance test; Among them, the electromagnetic performance testing system is used to measure the electromagnetic parameters such as hysteresis loop, magnetic permeability, resistivity, etc. of the composite materials of each formula, and evaluate their ability to respond to changes in the leakage magnetic field of the power transformer; the dielectric performance testing system is used to test the dielectric constant and dielectric loss of composite materials under different formulas; a triboelectric testing device is constructed to simulate the friction contact in the actual working environment, and measure parameters such as the amount of charge, output voltage and current generated by the composite materials during the friction process to evaluate their triboelectric conversion efficiency; through mechanical testing methods such as stretching, compression, and bending, the fatigue resistance, toughness and long-term stability of the composite materials are evaluated to ensure their reliability in complex working environments.
[0024] The following operations are performed before the triboelectric performance test: a high-performance vertical contact-separation mode friction nanogenerator structure is constructed, a composite material is used as the positive friction layer material, and a suitable negative friction layer material is selected by comparing the output performance or surface energy of the friction nanogenerator; the positive friction layer material and the negative friction layer material are circular specimens with a diameter of 55 mm, and the negative friction layer material is one of ethylene fluoride copolymer, polyimide, and polytetrafluoroethylene.
[0025] S22. Statistically analyze the results of the performance test, and use a suitable mathematical model or optimization algorithm to find the best balance between electromagnetic performance, triboelectric performance and mechanical stability, so as to screen out the optimal formula; The content of graphene oxide is limited to 0.2% to 1.2% (preferably 0.5% to 0.8%) of the total mass of the composite material to ensure that it can effectively enhance the triboelectric properties in the composite material without reducing the mechanical stability or electromagnetic properties due to excessive content. The content of cobalt ferrite is limited to 0.2% to 1% (preferably 0.2% to 0.6%) of the total mass of the composite material to optimize its electromagnetic response characteristics and synergize with graphene oxide to improve the overall performance of the composite material.
[0026] Figure 2The hysteresis loops of composite materials under different formulations. With the increase of cobalt ferrite in the formulation (from 0.2wt.% to 1wt.%), the residual magnetization and saturation magnetization of the composite material show a gradual increasing trend, which indicates that the hysteresis loop performance of the material has been significantly improved.
[0027] S23. Conduct stability and durability tests on the composite materials with the best formula to ensure the reliability and stability of the test results.
[0028] S3. Using the composite material with the best formula screened out, a composite nanogenerator is prepared. The specific operation is as follows: S31. Process the composite material with the best formula into a friction layer of a specific shape and size to ensure that its surface is smooth and has high mechanical strength, suitable for long-term operation; S32. Design and prepare the electromagnetic induction coil, and select the appropriate wire diameter, number of turns and layout to ensure that the coil can effectively induce current in the transformer leakage magnetic field; S33, assembling the friction layer and the electromagnetic induction coil according to a preset layout and position to form a composite structure, such as Figure 3 shown.
[0029] The friction layer is exposed to an environment that may generate vibration, and the electromagnetic induction coil is placed close to or near the transformer to detect the leakage magnetic field. The structure should reasonably arrange the electromagnetic induction element and the friction layer to ensure that the two can work together to maximize the energy conversion efficiency. The energy conversion efficiency of the generator can be optimized by adjusting the relative position, contact area, friction mode and other parameters between the friction layer and the electromagnetic induction element.
[0030] S34. Electrically connect and package the composite structure to obtain a composite nanogenerator, ensuring that the triboelectric effect and electromagnetic induction effect can be independently and synergistically converted into electrical energy output, while protecting the internal components from environmental factors.
[0031] The present invention provides an application of a composite nanogenerator based on bacterial fiber composite materials. When the transformer winding is deformed or short-circuited between turns, it will directly affect the winding current, thereby causing a significant change in the leakage magnetic field inside the transformer. It is crucial to identify winding defects by clarifying the distribution of leakage magnetic fields near the windings under normal operation of the transformer and various defects. The changes in the leakage magnetic field corresponding to different fault types are different. Therefore, in order to accurately analyze the fault type of the transformer, the embodiment constructs a friction-electromagnetic composite nanogenerator to sense the change in the transformer leakage magnetic field, and finally determines the fault type of the transformer.
[0032] The application of the composite nanogenerator prepared by the above preparation method in transformer leakage magnetic field monitoring comprises the following steps: S1. Integrate the prepared friction-electromagnetic composite nanogenerator into the power transformer monitoring system. During the integration process, it is necessary to ensure that the generator fits tightly with the leakage magnetic field area of the power transformer so as to effectively capture the magnetic field changes and convert them into electrical energy. S2. Connect the composite nanogenerator to the signal processing system to collect and analyze the power fluctuation data output by the generator in real time, including key parameters such as voltage, current, and power. In order to ensure the accuracy and reliability of the data, the collected raw data needs to be preprocessed, including denoising, filtering, calibration and other steps to eliminate the impact of environmental interference and measurement errors on data analysis.
[0033] S3. Through algorithm processing, the power fluctuation data (including the frequency, amplitude, phase difference, etc. of power fluctuation) is converted into the strength and direction information of the transformer leakage magnetic field, so as to realize the online monitoring, fault warning and performance evaluation of the leakage magnetic field state of the power transformer. Among them, by comparing the characteristic parameters with the threshold or mode of the normal state or fault state, it can be judged whether the transformer has leakage magnetic field anomalies, and further determine the type, degree and location of the anomaly. At the same time, a visual interface is provided to display real-time data and historical trends.
[0034] S4. Further use time series analysis, machine learning prediction models and other methods to predict the leakage magnetic field change trend in the future based on historical data and current status. Once a possible fault risk or abnormal state is found, an early warning signal is issued in time so that the operation and maintenance personnel can take corresponding measures to intervene and repair.
[0035] S5. Establish a complete data management system to store, manage and visualize the collected power data and analysis results. Through data visualization tools, complex power fluctuations and leakage magnetic field states are intuitively presented to operation and maintenance personnel in the form of charts, curves, etc., helping them to understand the working status and potential problems of the transformer more quickly and accurately.
[0036] The present invention provides a device for monitoring the leakage magnetic field of a power transformer, such as Figure 4 As shown, the following equipment is included: A composite nanogenerator prepared by the above-mentioned preparation method; Signal processing system, used to collect and analyze the power fluctuation data output by the generator; A processor, for processing the signal and converting the data into status information of the transformer leakage magnetic field; The operation interface is used to display the real-time data and historical trends of the transformer leakage magnetic field, as well as to perform fault warning and performance evaluation.
[0037] The operation interface has various operation instructions. When the executable instructions are executed, the processor executes a composite nanogenerator based on bacterial cellulose composite material and its application in power transformer leakage magnetic field monitoring as in the above embodiment. The operation interface instructions are configured as follows: According to the change of the output result of the friction-electromagnetic composite nanogenerator, the change degree of the leakage magnetic field is determined; according to the change degree of the leakage magnetic field, the fault type of the transformer is determined.
[0038] Therefore, the present invention adopts the preparation method and application of the above-mentioned bacterial cellulose-based composite nanogenerator, which utilizes the excellent mechanical properties of bacterial cellulose composite materials and the special effects of nanomaterials to convert mechanical energy and electromagnetic energy into electrical energy, and realizes real-time monitoring of the transformer leakage magnetic field by monitoring electrical energy fluctuations.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a bacterial cellulose-based composite nanogenerator, characterized in that: The following steps are involved: S1. Graphene oxide and cobalt ferrite are embedded in bacterial cellulose matrix through solution blending technology to prepare a structurally stable composite material; S2. Systematically evaluate the electromagnetic properties, triboelectric properties and mechanical stability of composite materials of various formulas to select the optimal formula; S3. Prepare composite nanogenerators using composite materials with optimal formulas screened out.
2. The method for preparing a bacterial cellulose-based composite nanogenerator according to claim 1, characterized in that: The S1 specifically includes: S11, cutting the bacterial cellulose hydrogel into block samples of 2×2 cm, stirring for 30 min using a high shear dispersing homogenizer to prepare a 10 mg / mL bacterial cellulose aqueous solution; S12, dispersing predetermined amounts of graphene oxide powder and cobalt ferrite powder in appropriate solvents to form uniform graphene oxide suspension and cobalt ferrite suspension; S13, mixing the prepared graphene oxide suspension and the cobalt ferrite suspension in an optimal ratio, and further dispersing them by ultrasonic treatment to obtain a mixed suspension in which nanoparticles are evenly distributed; S14, slowly adding the obtained mixed suspension into the bacterial cellulose aqueous solution, and continuing stirring to make the graphene oxide and cobalt ferrite evenly embedded in the bacterial cellulose matrix to obtain a mixed solution; S15, pouring the mixed solution into a mold for vacuum defoaming treatment for 10 minutes, and performing heating and drying treatment, thereby preparing a composite material with stable structure and excellent performance.
3. The method for preparing a bacterial cellulose-based composite nanogenerator according to claim 2, characterized in that: The limiting conditions for uniformly embedding graphene oxide and cobalt ferrite in the bacterial cellulose matrix in S14 include: the content of graphene oxide is limited to a range of 0.2% to 1.2% of the total mass of the composite material; the content of cobalt ferrite is limited to a range of 0.2% to 1% of the total mass of the composite material.
4. The method for preparing a bacterial cellulose-based composite nanogenerator according to claim 3, characterized in that: The limiting conditions for uniformly embedding graphene oxide and cobalt ferrite in the bacterial cellulose matrix in S14 include: the content of graphene oxide is limited to a range of 0.5% to 0.8% of the total mass of the composite material; the content of cobalt ferrite is limited to a range of 0.2% to 0.6% of the total mass of the composite material.
5. The method for preparing a bacterial cellulose-based composite nanogenerator according to claim 1, characterized in that: The S2 specifically includes: S21. Conducting systematic performance tests on the composite materials prepared by each formula, including electromagnetic performance test, dielectric performance test, triboelectric performance test and mechanical performance test; S22. Statistically analyze the results of the performance test, and use a suitable mathematical model or optimization algorithm to find the best balance between electromagnetic performance, triboelectric performance and mechanical stability, so as to screen out the optimal formula; S23. Conduct stability and durability tests on the composite materials with the best formula to ensure the reliability and stability of the test results.
6. The method for preparing a bacterial cellulose-based composite nanogenerator according to claim 5, characterized in that: The S21 includes the following operations before the triboelectric performance test: A high-performance vertical contact-separation mode friction nanogenerator structure is constructed, and the composite material is used as the positive friction layer material. By comparing the output performance or surface energy of the friction nanogenerator, the appropriate negative friction layer material is selected.
7. The method for preparing a bacterial cellulose-based composite nanogenerator according to claim 6, characterized in that: The positive friction layer material and the negative friction layer material are circular samples with a diameter of 55 mm, and the negative friction layer material is one of ethylene fluoride copolymer, polyimide, and polytetrafluoroethylene.
8. The method for preparing a bacterial cellulose-based composite nanogenerator according to claim 1, characterized in that: The S3 specifically includes: S31, processing the composite material with the best formula screened out into a friction layer with a specific shape and size; S32. Design and prepare electromagnetic induction coils, and select appropriate wire diameters, number of turns, and layout; S33, assembling the friction layer and the electromagnetic induction coil according to a preset layout and position to form a composite structure; S34, electrically connecting and packaging the composite structure to obtain a composite nanogenerator.
9. An application of a composite nanogenerator based on bacterial fiber composite material, characterized in that: Application of the composite nanogenerator prepared by the preparation method according to any one of claims 1 to 8 in transformer leakage magnetic field monitoring.
10. A device for monitoring leakage magnetic field of a power transformer, characterized in that: Includes the following equipment: A composite nanogenerator prepared by the preparation method according to any one of claims 1 to 8; Signal processing system, used to collect and analyze the power fluctuation data output by the generator; A processor, for processing the signal and converting the data into status information of the transformer leakage magnetic field; The operation interface is used to display the real-time data and historical trends of the transformer leakage magnetic field, as well as to perform fault warning and performance evaluation.
Citation Information
Patent Citations
Preparation method of bacterial cellulose based composite membrane with electromagnetic function
CN106519275A